Applicability of the primary care information system in nurses’ daily lives - Roseanny Marques de Queiroga; Ankilma do Nascimento Andrade; Kennia Sibelly Marques de Abrantes; Tarciana Sampaio Costa; Maura Vanessa Sobreira; Geofabio Sucupira Casimiro (Rev Rene)
The objective of this research was to investigate the applicability of the Primary Care Information System in the daily lives of nurses working in the Family Health Strategy. It is a study with qualitative approach carried out at the Health Department of Sousa-PB, Brazil. Data were collected through interviews in September and October 2010 and then submitted to content analysis. The following categories were identified: Purpose of the System in Family Health Strategy; Information recorded through the same; Nurses’ perceptions on their work in facility management regarding the System; Failures and difficulties in the use of forms and reports; Use of the System for planning the work process of the unit and moments or situations considered basic for making decisions concerning the information from the System. It was so concluded that the applicability in the work process of such professionals was merely limited to filling in forms and reports monthly, which did not correspond to the objectives proposed by the Ministry of Health.